Proceedings of the 8th International Conference on Model-Driven Engineering and Software Development 2020
DOI: 10.5220/0009097601260136
|View full text |Cite
|
Sign up to set email alerts
|

Guarded Deep Learning using Scenario-based Modeling

Abstract: Deep neural networks (DNNs) are becoming prevalent, often outperforming manually-created systems. Unfortunately, DNN models are opaque to humans, and may behave in unexpected ways when deployed. One approach for allowing safer deployment of DNN models calls for augmenting them with hand-crafted override rules, which serve to override decisions made by the DNN model when certain criteria are met. Here, we propose to bring together DNNs and the well-studied scenario-based modeling paradigm, by expressing these o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Although vanilla SBM has been successfully used in various contexts, in recent years it was shown that it may fall short in expressing various complex interactions between scenario objects (Katz et al, 2019;Katz, 2020;Elyasaf, 2020). Specifically, the simple event declaration mechanism -a finite set of events E, and a finite set of requested, waited-for and blocked events in every state, may be inadequate for expressing more complex behaviors.…”
Section: Scenario-based Modeling With Rich Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although vanilla SBM has been successfully used in various contexts, in recent years it was shown that it may fall short in expressing various complex interactions between scenario objects (Katz et al, 2019;Katz, 2020;Elyasaf, 2020). Specifically, the simple event declaration mechanism -a finite set of events E, and a finite set of requested, waited-for and blocked events in every state, may be inadequate for expressing more complex behaviors.…”
Section: Scenario-based Modeling With Rich Eventsmentioning
confidence: 99%
“…Recently, it has been observed that while SBM is well equipped for modeling reactive systems, it is sometimes inadequate for modeling systems that handle data -for example, robotics and autonomous vehicle systems (Katz et al, 2019;Katz, 2020), which involve various mathematical computations in addition to their reactivity. To this end, researchers have extended the SBM principles, allowing the event selection mechanism to support rich events, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In another recent project [13], we demonstrated how SBP can be used for guarding DNN-based systems. Specifically, we targeted state-of-the-art computer network systems, and demonstrated how manually-crafted scenarios could be used to correct various bugs discovered, e.g., through verification [16].…”
mentioning
confidence: 99%
“…choose a low sending rate even though higher rates could be used. Thus, we augmented this system with SBP components that ensured that this did not happen, by identifying such a situation and forcing the system to try out a higher sending rate [13]. In another example, we studied a DNN-based resource manager [17]: a system that controls CPU and memory resources, and assigns them to incoming jobs in order to maximize throughout.…”
mentioning
confidence: 99%
See 1 more Smart Citation